Arabic Teaching at Islamic Boarding School from The Perspective of Post-Method Era Parameters/Ta’lim al-Lughoh al-‘Arabiyah fi al-Ma‘ahid Min Mandzur Ma‘ayir Ashr Ma Ba‘da al-Thariqah - Wahida, Besse; Sabaruddin Garancang; Amrah Kasim; Hania (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2025)
This research examined the analysis the process of Arabic teaching from the post method era perspective at Islamic boarding schools. The post-method era concept introduces three post-method parameters that guide teachers to develop their own teaching methods and techniques by synthesizing knowledge and teaching experiences without depending on a particular method. This is different from the reality of Arabic teaching in some traditional or modern Islamic boarding schools that still rely on the use of particular method. Therefore, the researchers chose the research place in public Islamic boarding schools that provide formal and non-formal teaching. The importance of this research lies in the fact that the concept of post method has been widely studied and researched in the other foreign languages teaching. While in Arabic education, it is still in limited studies. A qualitative research was used with case study approach in three Islamic boarding schools in Pontianak City. The data were collected by participatory observation in the formal and non-formal Arabic teaching process in grades XI and XII of Aliyah, in-depth interviews with all teachers of Arabic subject, and documentation, then analyzed using descriptive analysis and pattern-matching techniques. The research found that the Arabic teaching at Islamic boarding schools had applied the three post-method parameters in many instruction activities that can be seen in exploratory, collaborative, interactive, and reflective instruction activities. The result of research was expected to provide an overview and information about several Arabic teaching activities in Islamic boarding schools that are suitable for post method teaching.